2017
DOI: 10.1017/jog.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted surface mass balances of debris-free glaciers observed between the southern and the inner parts of the Everest region (2007–15)

Abstract: ABSTRACT. Three debris-free glaciers with strongly differing annual glaciological glacier-wide mass balances (MBs) are monitored in the Everest region (central Himalaya, Nepal). The mass budget of Mera Glacier (5.1 km 2 in 2012), located in the southern part of this region, was balanced during 2007-15, whereas Pokalde (0.1 km 2 in 2011) and West Changri Nup glaciers (0.9 km 2 in 2013), ∼30 km further north, have been losing mass rapidly with annual glacier-wide MBs of −0.69 ± 0.28 m w.e. a −1 (2009-15) and −1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 61 publications
8
89
0
Order By: Relevance
“…We use the same glacier tongue outline as Vincent et al (2016), which was derived from a combination of UAV imagery, field measured velocity fields and field expertise. It is different from the outline available in the Randolph Glacier Inventory 6.0 (Pfeffer et al, 2014), which includes the nearby West Changri Nup Glacier in the same outline (Sherpa et al, 2017). The debris-covered part…”
Section: Study Areamentioning
confidence: 95%
“…We use the same glacier tongue outline as Vincent et al (2016), which was derived from a combination of UAV imagery, field measured velocity fields and field expertise. It is different from the outline available in the Randolph Glacier Inventory 6.0 (Pfeffer et al, 2014), which includes the nearby West Changri Nup Glacier in the same outline (Sherpa et al, 2017). The debris-covered part…”
Section: Study Areamentioning
confidence: 95%
“…a -1 ) between 2010 and 2015, while Pokalde and Changri Nup glaciers, in the nearby interior of the range, showed a rapid wastage of -0.63 and -1.24 m w.e. a -1 , respectively, over the same period (Supplementary Table S6, Sherpa and others, 2017). Given the limited number of modeled mass-balance series for mean mass-balances computation, we believe these means should not be considered as regional representative and must be handled cautiously.…”
Section: Mass Balances Of Six Glaciers Are Dubious (Supplementarymentioning
confidence: 99%
“…It has been reported that glaciers have been retreating rapidly since the 1850s [14]. In the case of the Hindu Kush Himalaya (HKH) region, many studies have concluded the shrinkage and fragmentation of the glaciers [5,15,16], whereas slight mass gain has been observed in the Karakoram region in recent studies [17,18]. Most glaciers in the Eastern and Central Himalaya belong to the summer-accumulation type, gaining mass mainly from summer-monsoon snowfall, whereas winter accumulation is more important in the Northwest [5,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various glaciological studies have been carried out in the Yala Glacier since the 1980s [30,37]. French researchers also initiated the MB measurements on the Mera Glacier in 2007 and Pokalde in 2009 [16,38]. Kathmandu University together with the International Centre for Integrated Mountain Development (ICIMOD) has been conducting continuous MB measurements in the Yala Glacier since 2011 [37].…”
Section: Introductionmentioning
confidence: 99%